The Application of Paintings on Cutting Boards in Terms of the Principles of Fine Arts for Grade XI Students at SMA Dharma Pancasila Medan - harahap, zety shafitri; Mesra, Mesra; Azis, Adek Cerah Kurnia; Rajudin, Rajudin; Sugito, Sugito (V-art: Journal of Fine Art, 2024)
This study aims to evaluate the application of painting techniques on cutting board media based on the principles of fine arts among grade XI students at SMA Dharma Pancasila Medan. The research employs a qualitative descriptive method. The study involved 30 grade XI students specializing in painting. Data were collected through documentation, practical tests, and observations. The findings reveal the following average scores: 82.78 for the principle of unity (fairly good), 82.84 for the principle of balance (fairly good), 81.81 for the principle of rhythm (fairly good), 81.68 for the principle of emphasis (fairly good), 84.12 for the principle of proportion (good), and 82.32 for the principle of harmony (fairly good). These results indicate that the students demonstrated a fairly good ability to apply the principles of fine arts in their painting projects on cutting board media during the 2024–2025 academic year.